Designing an Electronic Citizen Relationship Management Model in the Social Security Organization Based on the S-O-R Approach - Javan Javidan, Sara; Marjani, Amirbabak; Hajalian, Farshad; Moradi haghighi, Mansoureh (Digital Transformation and Administration Innovation, 2026)
The purpose of the present study is to design a model of electronic citizen relationship management in the Social Security Organization using the S-O-R (Stimulus–Organism–Response) approach (case study: Social Security Organization). In this regard, after reviewing the concepts of electronic customer relationship management, the notion of citizenship, and the Stimulus–Organism–Response framework, a qualitative method was employed to identify the indicators and components of the electronic relationship management model and to design the proposed framework. The study population consisted of experts and university professors in the fields of management and marketing. A sample of 10 experts in this domain was selected using the snowball sampling method. Data collection was conducted through expert interviews using the Delphi technique. Data analysis was performed through coding procedures in MAXQDA software. The findings revealed that the electronic citizen relationship management model in the Social Security Organization based on the S-O-R approach includes five main themes, six subthemes, and forty final indicators confirmed by experts. These themes include: (1) marketing strategies; (2) environmental factors (website); (3) external organizational factors (social and cultural, economic); (4) perceived experience (perceived value, perceived quality, perceived security, and perceived ease of use); and (5) citizens’ behavioral responses and reactions (e-loyalty, interactions, and information sharing).